Embryonic and larval development and fatty-acid profile of Epinephelus marginatus spawned in captivity: tools applied to captive rearing - Mello, P. H.; Araujo, B. C.; Campos, M. F.; Rodrigues-Filho, J. A. [UNESP]; Garcia, C. E. O.; Moreira, R. G. (Wiley-Blackwell, 2018)
Development, ontogeny of the digestive system and the fatty-acid (FA) profile, were analysed during development of Epinephelus marginatus. Larvae were analysed 7 and 17days post fertilization (dpf) to evaluate fatty-acid profile and morphological variables, respectively. Epinephelus marginatus larvae have relatively slow development of digestive structures, but were able to capture, ingest and digest prey by 5 dpf. Eggs were composed of high percentages of polyunsaturated fatty acids (PUFA) in phospholipids. The percentage of n3 PUFAs was higher than n6, especially docosahexaenoic acid (DHA), which exhibited higher levels compared with other marine species during the first 3days of development, both in terms of phospholipids and triglycerides. The larvae present a high content of docosahexaenoic acid-eicosapentaenoic acid (DHA-EPA) and, during this phase, live food of small size was required (copepods or SS-strain Brachionus rotundiformes), enriched with DHA-EPA. These results may guide future studies on the contribution of FAs required during this stage of the life cycle of E. marginatus, to advance knowledge of the use of these FAs throughout ontogeny and contribute to the culture of this species commercial production or restocking.
Keywords: digestive system; embryogenesis; Epinephelus marginatus; morphology; phospholipids; triglycerides